Taxonomy and phylogeny of the genus Ganoderma (Polyporales, Basidiomycota) in Costa Rica - Mardones Hidalgo, Melissa (2023)
Ganoderma species are well recognized by their significant role in the recycling of nutrients in ecosystems, and by their production of secondary metabolites of medical and biotechnological importance. Ganoderma spp. are characterized by laccate and non-laccate, woody basidiocarps, polypore hymenophores, and double-walled basidiospores generally with truncate apex. Despite the importance of this genus, its taxonomy is unclear, and it includes several species’ complexes with few circumscribed species, and incorrect geographic distributions. The aim of this work was to provide detailed morphological descriptions together with phylogenetic analyses using ITS sequences to confirm the presence of seven species of Ganoderma in Costa Rica: G. amazonense, G. applanatum s.l., G. australe, G. curtisii, G. ecuadorense, G. oerstedii and G. parvulum. This is the first study that integrates morphological and phylogenetic data of Ganoderma from Central America, and a key of the neotropical species. Besides, the distribution range of G. curtisii, previously reported from North America, and G. ecuadorense from South America, is expanded to Central America.